2022
DOI: 10.3390/su14031253
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Road Crashes with Animals in Poland

Abstract: This article describes the issue of the influences of the time factor and wildlife populations on road animal–vehicle crashes. The article presents problems associated with animal–vehicle crashes in Poland. They are the subject of many court disputes. For the purposes of the study, data on animal–vehicle road crashes were obtained from the SEWiK database, as well as data on the numbers of animals in hunting districts from 2016–2020. The relationship between the number of road crashes and time was analysed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, it is worth noting that the temporal/spatial patterns are not identical for all types of accidents. Krukowicz et al [60] found no impact on animal-vehicle crashes during the lockdown in the initial period of the COVID-19 pandemic (March-April 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that the temporal/spatial patterns are not identical for all types of accidents. Krukowicz et al [60] found no impact on animal-vehicle crashes during the lockdown in the initial period of the COVID-19 pandemic (March-April 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unavailability of such records, the effects of driving and environmental factors in crash occurrences cannot be brought to light. Furthermore, animal-vehicle collision is an important factor to be considered both for Bangladesh and other countries of the world [64,65]. In future research, the impact of containment strategies on animal-vehicle collisions can be addressed.…”
Section: Limitationmentioning
confidence: 99%
“…Temporal and spatiotemporal analyses of the roadkill were carried out in many counties around the globe [1][2][3], in European countries [4][5][6][7], including those close to Lithuania [8][9][10][11]. Roadkill recording by citizen scientists was used as a part of worldwide projects on roadkill data collection [12], and these projects were successful in several countries [13,14].…”
Section: Introductionmentioning
confidence: 99%